Antibacterial Efficacy of Polymer Coated Ceramic Microparticles loaded with a novel combination of antibiotics on the Enterococcus Faecalis Biofilm - Zargar, Nazanin; Parhizkar, Ardavan; Nasiri, Mohammad Javad; Saedi, Sara (Iranian Endodontic Journal, 2023)
Introduction: Nano-technology applied for the local delivery of different agents and/or drugs has made its path to endodontics. In the current study, the antibacterial efficacy of biopolymer-coated ceramic microparticles loaded with a modified combination of triple antibiotics, i.e. Penicillin G, Metronidazole and Ciprofloxacin (PMC), was evaluated against two strains of Enterococcus faecalis (E.faecalis); a standard clinical strain obtained from previously root-filled teeth with persistent periapical lesions, and compared to the most common antimicrobials used in endodontics. Methods and Materials: After synthesis of the polymer-coated microparticles loaded with antibiotics, the 21-day release of antibiotics were evaluated and a stock solution was produced using the maximum released amount of drugs and distilled water. The antibacterial activity of PMC, triple antibiotic paste (TAP), calcium hydroxide (CH), chlorhexidine (CHX) and sodium hypochlorite (NaOCl) against two bacterial strains was determined using “Minimum Inhibitory Concentration” and “Agar Diffusion Test”. Additionally, “Microtiter Plate Assay” was performed to assess anti-biofilm properties. Results: Minimum inhibitory concentration values reported for TAP and PMC were 1/256. PMC showed the maximum diameter of growth inhibition in both strains (33 mm and 35 mm), while CH had the minimum diameters (13 mm and13 mm). Based on microtiter plate assay, TAP showed higher biofilm formation than PMC. Biofilm formation was higher in the standard strain for PMC; however, NaOCl, CHX and CH completely inhibited biofilm formation. Conclusions: Based on the findings of the present study, it could be concluded that PMC and TAP were the most effective medicaments against E.faecalis in its planktonic form; however, none could inhibit its biofilm formation. Further studies using larger sample size and “Confocal Scanning Laser Microscopy” are recommended.